Above the clouds : status culture of the modern Japanese nobility - Lebra, Takie Sugiyama, 1930- (University of California Press, 1993)
This latest work from Japanese-born anthropologist Takie Sugiyama Lebra is the first ethnographic study of the modern Japanese aristocracy. Established as a class at the beginning of the Meiji period, the kazoku ranked directly below the emperor and his family. Officially dissolved in 1947, this group of social elites is still generally perceived as nobility. Lebra gained entry into this tightly knit circle and conducted more than one hundred interviews with its members.